A Rare Case: Tuberculous Peritonitis, Encapsulating Peritoneal Sclerosis, and Incisional Hernia in Continuous Ambulatory Peritoneal Dialysis Patient - Kurniaatmaja, Enita R.; Bandiara, Ria; Oktaviyanti, Ika Kustiyah; Rudiansyah, Mohammad (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Peritonitis is the most common infectious complication of peritoneal dialysis (PD) with an estimated ratio of 1:20–30 patients per month. In addition, less than 3% cases are due to Mycobacteria, although not all are caused by Mycobacteria tuberculosis. Therefore, specific examinations are needed for proper diagnosis. Encapsulating peritoneal sclerosis (EPS), another rare complication of PD, accounts for 0.7–13.6 per 1000 patients per year. CASE REPORT: A 37-year-old man undergoing PD, with complaints of intermittent abdominal pain and cloudy fluid, followed by nausea, vomiting, and constipation. Furthermore, visible protrusion was observed on the abdominal wall due to the wound from the Tenckhoff catheter insertion surgery. This is clearly comprehended as the patient sits or stands but disappears on lying down. Along with the condition, continuous ambulatory PD (CAPD) ultrafiltration ability decreases, rough defecation occurs, with a hard sensation on the lower right abdomen. Moreover, the patient had earlier suffered peritonitis for the 3rd time. The results of the dialysate fluid analysis showed a cloudy liquid coloration, as the number of cells 278, polymorphonuclear 87, mononuclear 13, Ziehl–Neelsen +1 and acid-resistant bacteria +3 staining, including GeneXpert MTB/RIF, were positive. Furthermore, abdominal computed tomography (CT) scan revealed a thick peritoneum, partly with calcification, air-filled intestinal, dilated colon with wall thickening. Furthermore, the mesentery lining the liver and intestine were observed to be dense with multiple calcifications to support an EPS. Definitive diagnosis is confirmed by laparotomy and/or laparoscopy, but CT scan provides an alternative. Subsequently, CAPD utilization is discontinued and switched to renal replacement therapy to hemodialysis twice a week due to several complications associated with PD, ranging from recurrent peritonitis, tuberculous peritonitis, EPS, and incisional hernias responsible for an ineffective PD ultrafiltration. CONCLUSION: At present, the combination of clinical symptoms, radiology, and medical pathology remains the key to diagnosing tuberculous peritonitis and EPS. Consequently, prompt and precise analysis determines a good prognosis.